Sexualidade e trabalho: estudo sobre a discriminação de homossexuais masculinos em bancos públicos - Souza, Eloisio Moulin de (2009)
This thesis was developed trying to analyze the possible forms of discrimination in work related to male homosexual employees who work in public banks located in the metropolitan area of Vitória-ES under the point view of the poststructuralism. Thus, there was a bibliography on the international and national research and related that involve the study of male homosexuality with the world of work and an analysis of differences between the traditional approach that involves the study of gender analysis for a post-structuralism analysis. Regarding methodological aspects, the type of research is qualitative, using a semi-structured script, simple observation, documentary research, field diary and informational interviews to collect data. We interviewed eight employees of federal banks. For the analysis of data was used the analysis of discourse developed by Michel Foucault and analysis of documents. It follows that the interviewees are targets of direct and indirect discrimination on grounds of their sexuality. The direct discrimination manifests itself in the deficiency of normative public banks studied to ensure real and clarify the rights of workers. However, the most uncomfortable question to respondents are the expressions of indirect discrimination by: (a) pejorative jokes that speak more generally about homosexuals, (b) isolation not to having contact with customers and even to other employees; (c) working conditions inferior to those offered to other employees, (d) exclusion from participation in informal groups and activities of these groups occurred outside the company, (e) games, gossip and ironies on how to walk, talk and gestures when are not present in the enclosure, (f) name calling related to the alleged disclosure of a woman belonging to homosexuals ("sissy", "deer"), (g) difficulties in career growth, (h) difficulty of hiring managers by homosexuals companies providing services to public banks.